2021
DOI: 10.1093/plcell/koab006
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur transfer from the endophytic fungus Serendipita indica improves maize growth and requires the sulfate transporter SiSulT

Abstract: A deficiency of the essential macronutrient sulfur leads to stunted plant growth and yield loss; however, an association with a symbiotic fungus can greatly improve nutrient uptake by the host plant. Here, we identified and functionally characterized a high-affinity sulfate transporter from the endophytic fungus Serendipita indica. SiSulT fulfills all the criteria expected of a functional sulfate transporter responding to sulfur limitation: SiSulT expression was induced when S. indica was grown under low-sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 74 publications
3
39
0
Order By: Relevance
“…These results suggest that Sultr exhibits species specificity. Moreover, several studies confirmed that the overexpression of Sultr genes could improve plant growth under low-S conditions by upregulating the genes involved in the S assimilation pathway and promoting the biosynthesis of essential amino acids and S-containing compounds (Ding et al, 2016;Narayan et al, 2021). In our study, under low-S conditions, the overexpression of MhSultr3;1a in apple calli resulted in better growth (Figure 7C) and higher fresh weight (Figure 7D).…”
Section: Discussionsupporting
confidence: 76%
“…These results suggest that Sultr exhibits species specificity. Moreover, several studies confirmed that the overexpression of Sultr genes could improve plant growth under low-S conditions by upregulating the genes involved in the S assimilation pathway and promoting the biosynthesis of essential amino acids and S-containing compounds (Ding et al, 2016;Narayan et al, 2021). In our study, under low-S conditions, the overexpression of MhSultr3;1a in apple calli resulted in better growth (Figure 7C) and higher fresh weight (Figure 7D).…”
Section: Discussionsupporting
confidence: 76%
“…Metal uptake from soil or mobilization to other plant parts involves different transporters localized at the plasma membrane and envelope membranes of cell organelles such as the vacuole, mitochondria, and plastids. Notably, plants have a sensing system for maintaining metal homeostasis in which transporters work as receptors plus transporter, that is, transceptors (Cointry & Vert, 2019; Narayan et al 2020; Narayan et al, 2021; Yadav et al, 2021b). The bioavailability of metal ions in soil and their scarcity in the cytosol can be sensed by transceptors, which leads to the regulation of metal ions uptake via low or high‐affinity transporters.…”
Section: Metal Transport In Plants and Its Mechanismmentioning
confidence: 99%
“…The root endophyte Serendipita indica (formerly known as Piriformospora indica, order Sebacinales, phylum Basidiomycota) has been extensively used in studying plant-fungal interactions [14][15][16]. S. indica is an axenically cultivable fungus, able to colonise a wide range of plant species.…”
Section: Introductionmentioning
confidence: 99%